Soup cost $10 for 3 cans. Josh spent $40 on soup. How many cans did he buy?

Answers

Answer 1
Answer: he bought 12 cans:) because if 3 cans are 10$ and he spent 40$ just multiply 4 (the 40 dollars)times 3 (the amount of cans you get per 10 dollars).Hope this helped!

Related Questions

Choose 3 of the following that are NOT equivalent to the expression below 1/2✖️7 A.) 1✖️7➗2 B.) 1 ➖ 2✖️7 C.)1✖️7✖️2 D.)1✖️7 ➖ 2 E.) 14
Russell collected 30 stones at his grand parents' house. He decided to give his little sister 1 / 5 of the stones. How many stones did he give his sister?
How can you tell 7/10 is greater than 1/2
A grocery store so the six pack of bottled water for $3.79 a 12 pack for $6.89 which package cost The least per bottle explain your reasoning
How many 1,1/3 yards fits into 15 yards

How are compare and order alike

Answers

Answer:

because they are and make sense

If x=7 and y=-3

12-5xy +9x2y + 15-2y2

Answers

Just plug in x = 7 and y = -3 in place of x and y, respectively

12-5xy +9x^2y + 15-2y^2\n\n12-5(7)(-3) +9(7)^2(-3) + 15-2(-3)^2\n\n12 - (-105) + (-1323) + 15 -18\n\n12 + 105 - 1323 + 15 - 18 = \boxed{-1209}

Your answer is -1209

What does the mode of this set of data represent?

Answers

It should be D because the mode is the value that occurs the most often. 

What type of property is this? (P×1)×6

Answers

indentity property, anything times 1= the same number so the answer is (p) times 6
then associative property of mult
note:a(b)=a times b and =ab

a(bc)=(ab)c
so (p)6=(p6)=6p

ken has 12.2-ounce bottle of ketchup. he uses 1/20 of the ketchup every time he has a buffalo burger. how many ounces of ketchup are left after LAN has eaten 4 buffalo burgers ?

Answers

Steps:
1. You do 1/20 times 4 which equals 1/5 (when simplified)
2. You convert 1/5 to 2/10 which can be turned into
.2
3. You do 12.2 minus .2
4. Your answer is
12 ounces

Find one point that lies in the solution set of the following system of inequalities:Y<(or equal)1/2x+6
y>-3x-1

justify answer

Answers

Simplify the first inequality.

Multiply 1/2 by x to get (1/2)x. 
y≤(1/2)x+6 and y>−3x−1 

Simplify. 
y≤x/2+6 and y>−3x−1

Since x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation. 
x/2+6≥y and y>−3x−1 

Because 
6 does not contain the variable to solve for, move it to the right-hand side of the inequality by subtracting 6from both sides. 
x/2≥−6+y and y>−3x−1 

Multiply both sides of the equation by 2. 
x≥−6⋅(2)+y⋅(2) and y>−3x−1 

Multiply −6 by 2 to get −12. 
x≥−12+y⋅(2) and y>−3x−1 

Multiply y by 2 to get y(2). 
x≥−12+y(2) and y>−3x−1 

Multiply y by 2 to get y⋅2. 
x≥−12+y⋅2 and y>−3x−1 

Move 2 to the left of the expression y⋅2. 
x≥−12+2⋅y and y>−3x−1 

Multiply 2 by y to get 2y. 
x≥−12+2y and y>−3x−1 

Reorder −12 and 2y. 
x≥2y−12 and y>−3x−1 



Simplify the second inequality.

Because x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation. 
x≥2y−12 and −3x−1<y 

Since −1 does not contain the variable to solve for, move it to the right-hand side of the inequality by adding 1 to both sides. 
x≥2y−12 and −3x<1+y 

Divide each term in the inequality by −3. When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign. 
x≥2y−12 and 3x/−3>1/−3+y/−3 

Cancel 3 in the numerator and denominator. 
x≥2y−12 and −(−1⋅x)>1/−3+y/−3 

Multiply −1 by x to get −1x. 
x≥2y−12 and −(−1x)>1/−3+y/−3 

Rewrite −1x as −x. 
x≥2y−12 and −(−x)>1/−3+y/−3 

Simplify
x≥2y−12 and x>−1/3+y/−3 


x≥2y−12 and x>−1/3y/3 


Point of intersection: (-2, 5)